Schadenfreude Scale: Construct Validity Test with Confirmatory Factor Analysis - Syahid, Achmad; Akbar, Muhamd Khalid; Irvan, Moh.; Moormann, Peter Paul (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2024)
This research aimed to investigates construct validity of Schadenfreude measurement instrument adapted for the Indonesian context. Schadenfreude, which is the feeling of satisfaction at another individual's misfortune, is explored through five dimensions, namely concern for justice, aggression, competition, arrogance, and envy. These dimensions guided the development of a 60-item instrument based on scale by Crysel and Webster (2018). Data were collected from 500 respondents in Pagutan Village, Mataram, Lombok, Indonesia, reflecting the social, cultural, and economic context. Confirmatory factor analysis (CFA) and measurement invariance using M-plus were conducted to test construct validity. The result showed that 10 items were invalid, leaving a refined instrument of 50 valid items across the dimensions. This validated instrument provided a robust tool to measure Schadenfreude in Indonesian populations aged > 12, with applications in social, political, economic, and competitive contexts. In conclusion, the research showed the cultural relevance of Schadenfreude in understanding human emotions and social behavior.